2021
DOI: 10.3390/su132212400
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Cycling among Secondary School Adolescents in an Ethnically Diverse City: The Perspective of Birmingham Transport Stakeholders

Abstract: Despite strategies and schemes to increase cycling among adolescents in England, the levels of cycling among secondary school adolescents in various cities is low. This study aims to understand the factors influencing cycling among Birmingham secondary school adolescents from the perspectives of local transport stakeholders promoting cycling among secondary school adolescents. In 2019, 14 local transport stakeholders promoting cycling among secondary school adolescents in Birmingham participated in a semi-stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
0
0
Order By: Relevance
“…Gravenstine et al (2022) revealed that support for infrastructure enhancements, enjoyment from riding, riding to spend time with friends and family, and the number of children in the household positively influenced intentions to travel by bicycle in New York, USA [40]. Fasan et al (2021) found that secondary school students in Birmingham, UK, felt more inclined to bicycle when their peers also bicycled [41].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gravenstine et al (2022) revealed that support for infrastructure enhancements, enjoyment from riding, riding to spend time with friends and family, and the number of children in the household positively influenced intentions to travel by bicycle in New York, USA [40]. Fasan et al (2021) found that secondary school students in Birmingham, UK, felt more inclined to bicycle when their peers also bicycled [41].…”
Section: Literature Reviewmentioning
confidence: 99%